Comparação entre o custo de capital aplicado pela ANEEL nas revisões tarifárias e o custo de capital das distribuidoras de energia elétrica para o período de 2015 a 2017 - Bueno, Emilene Francisco (Universidade Federal de São Carlos, 2018)
The formation of electric energy tariffs in Brazil involves a series of procedures and regulations, and the regulatory agency (ANEEL) role is to establish and review the methods adopted. One of the methodologies involved in the calculation of tariffs is the remuneration of the capital invested by distribution concessionaires in the sector, obtained through the regulatory capital cost determination (WACC). This cost is calculated during the tariff review processes to which the distributors are subject periodically, and directly influences the index of it repositioning passed on to the consumer, as well as serving as economic parameter for the investments in the sector. Considering the existence of specific aspects of regulatory acts in the calculation used by ANEEL, this work has as a goal to verify if the cost of regulatory capital and the cost of capital of the electric energy distributors, calculated from six different models, are statistically similar or if there is a possible overvaluation or devaluation of the index set by the regulatory agency. Because of the disclosure by ANEEL of two regulatory WACC values, a so-called "before tax" and "after tax", comparisons are made from the two indexes in order to verify their peculiarities. It is used as sample 10 electric power distribution companies from public capital that had their definitive processes of fee revision concluded during the triennium 2015-2017. To verify the hypothesis of this study, we performed analyzes of absolute and relative deviations and non-parametric single-sample tests (Wilcoxon's test). The results indicated that both the "before tax" regulatory WACC and the so-called "after tax" WACC are higher than the average results obtained for the capital cost from 10 distributors, but the first index (which is actually used in the remuneration distributors' capital) shows a greater discrepancy. These two ways of calculation and dissemination of indices "before" and "after tax" by the regulatory agency itself already is a difficulty factor in the process of comparison between the cost of regulatory capital and the calculated using other models. Watching the main objective, this research finds that the regulatory rate of return is generally overestimated by the regulator, that is, the State has provided the investor with a profitability higher than the adequate cost of capital. This causes a greater attractiveness for the investments, but it charges the consumer more by repositioning the tariffs. Finally, considering that ANEEL estimates the WACC for up to 3 years, it can be observed that the method used does not following the oscillations of the Brazilian economic market. This makes both investor or consumer be harmed or benefited, depending on the year analyzed.
Comparison between the cost of capital applied by ANEEL in tariff revisions and the cost of capital of electric energy distributors for the period from 2015 to 2017
Keywords: Setor Elétrico; Regulação; Revisão Tarifária; Custo de capital; Electric Sector; Regulation; Tariff Review; Cost of Capital; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS::ADMINISTRACAO FINANCEIRA; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS